Adapting roughages varying in quality and curing processes to the nutrition of beef cattle. - Smith, E.F.; Koch, B.A.; Cox, R.F.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
The hay used in this study consisted of good-quality, third-cutting alfalfa. It was cut, cured, and baled in the field and stored in a conventional hay shed. After having been in storage 2 months, a part of the alfalfa hay was removed from the barn, coarsely ground through a 1/4 -inch screen, made into3/8-inch pellets by a local feed processor, and stored for later feeding. The forage-type sorghum was field harvested in mid-October with the usual silage equipment. The loads were alternately ensiled in upright silos or dehydrated, finely ground, and pelleted into 3/8-inch pellets. These pellets were then stored ill bulk for later feeding. The prairie hay used was of good quality. It was grow a local farm meadow. Fifty head of choice-quality heifer calves from the Jeff Ranch, Fort Davis, Texas, were used in this experiment. They were allotted into five lots, 10 head per lot, on the basis of live weight. They were fed a winter ration consisting entirely of alfalfa hay or pellets and either sorghum silage or dehydrated pelleted sorghum for 126 days.
Keywords: Beef; Roughages; Curing; Nutrition